Facultad de Ciencias Administrativas, Gestión Empresarial e Informática tuvo defensa de trabajos de titulación - García García, Mariana (2023)
The 18 students that the faculty scheduled to defend their degree projects demonstrated the skills with which they were trained, verifying that the future professionals appropriated the knowledge due to the way they explained their cases, being the reason for praise and recognition from of the court that examined the students.